Re-fermentation of Green Liberica Coffee (Coffea Liberica) Beans: Impact on the Caffeine and Antioxidant Content of the Roasted Beans - Sunarharum, Wenny Bekti; Umami, Hindun Riza; Kartika, Annisa Aurora; Septiana, Siska; Mahatmanto, Tunjung (Graduate School, Universitas Brawijaya, 2023)
Coffee is renowned for its delightful taste and associated health benefits. A growing preference for lower-caffeine coffee is evident, but traditional decaffeination processes can inadvertently deplete vital bioactive compounds like antioxidants. This research explores the effects of re-fermentation on green liberica coffee beans to alter their caffeine and antioxidant levels. The re-fermentation was achieved using water and coffee cherry extract as media, while a control sample without re-fermentation was used for comparison. The study focused on caffeine content and antioxidant activity, measured as IC50. The results show that re-fermentation, whether with water or coffee cherry extract, led to decreased caffeine content and increased antioxidant activity. The re-fermentation process utilizing coffee cherry extract yielded the lowest caffeine content at 0.12% and exhibited the strongest antioxidant activity with an IC50 of 11.00 ± 1.21 ppm. Keywords: Antioxidant, caffeine, green coffee beans, liberica, re-fermentation.